'Failed Feminism': Anne Tyler's Vinegar Girl in the Chinese Market. - Duan, Yingjie; Tian, Junwu (Critical Survey)
In Vinegar Girl, a 2016 fictional adaptation of The Taming of the Shrew, Anne Tyler exhibits an ambivalent treatment of the female predicaments left by William Shakespeare: while she invests her modern version of Katherina with linguistic and intellectual independence emblematic of female resistance to patriarchal disciplines, she somehow acquiesces in the fixed familial place and the stereotypical images of women in the monolithic patriarchal system. When the novel was introduced into the Chinese mainland in 2017, the Chinese publisher, out of commercial concerns, advertised it as a highly feminist text through the delicate manipulation of the translation of its title and a series of paratextual manoeuvres, to the detriment of the novel's ambiguous complexities of gender issues. The marketing strategies nevertheless backfired on one of China's social media platforms and rendered the novel a relatively 'failed' feminist text against China's unique market and media background in the last decade.